1988
DOI: 10.1002/eji.1830181116
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive T cells in mercury‐induced autoimmunity. Demonstration by limiting dilution analysis

Abstract: Mercuric chloride is responsible in Brown-Norway rats for an autoimmune disease that is autoregulated. Previous studies have shown that this agent induces T cell-dependent polyclonal B cell activation in these rats. Evidence has also been obtained for the existence of autoreactive T cells which play a role in the evolution of this process. In the present study, limiting dilution analysis was used to demonstrate that (a) frequent autoreactive T helper cells which proliferate in the presence of T cells from HgCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…It has been previously reported that Brown Norway (BN) rats receiving sublethal doses of HgCl 2 develop an inflammatory syndrome (Pelletier et al, 1986;Rossert et al, 1988;Pusey et al, 1990). Recently, we have demonstrated that at-RA treatment significantly reduces the inflammatory response observed during HgCl 2 -induced nephritis in BN rats by inhibiting the cell infiltration into the renal interstitium as well as the release of proinflammatory mediators (Escribese et al, 2007).…”
mentioning
confidence: 68%
“…It has been previously reported that Brown Norway (BN) rats receiving sublethal doses of HgCl 2 develop an inflammatory syndrome (Pelletier et al, 1986;Rossert et al, 1988;Pusey et al, 1990). Recently, we have demonstrated that at-RA treatment significantly reduces the inflammatory response observed during HgCl 2 -induced nephritis in BN rats by inhibiting the cell infiltration into the renal interstitium as well as the release of proinflammatory mediators (Escribese et al, 2007).…”
mentioning
confidence: 68%
“…Recently, some progress has been made [39,40], in that bulk T cells of HgCl 2 -treated B10.S mice were found to react against a variety of different self proteins altered by Hg 2+ , in particular fibrillarin, a small ribonucleoprotein that is mainly located in the nucleolus and is the principal target of ANolA in these mice [41,42]. Moreover, in HgCl 2 -treated Brown Norway rats an activation of autoreactive CD4 + T cells has been described [43,44], albeit that the MHC II-associated self proteins recognized by them have not yet been identified; recent experimental evidence indicates that these cells are of the Th2 type [17] (P. Druet, personal communication). These and other findings [7,15,16,45,46] indicate that in animals susceptible to HgCl 2 -induced systemic autoimmune disease an activation of the immune system takes place that favours a Th2-like reaction.…”
Section: Discussionmentioning
confidence: 99%
“…While this is a theoretical possibility, it seems unlikely. In a study using limiting-dilution analysis for autoreactive T-lymphocytes in BN rats injected with HgCl 2 there was no further increase in the number of autoreactive T-lymphocytes from day 6 to day 14 after commencing injections of HgCl 2 suggesting that full recruitment of naïve cells had occurred by day 6 [38].…”
Section: Discussionmentioning
confidence: 97%